PERSEPSI MAHASISWA TERHADAP PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP MOTIVASI BELAJAR - An-Khofiyyah, Nida An-Khofiyyah; Farihatul Umi, Nabila; Pribadi, Raden Roro Jasmine Zhafirah; Mustopo, Daffa Nurhidayah Rizky; Muzaki, Helmi (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2024)
Social media has become a place for social interaction and expanding social networks. TikTok is one of Indonesia's most frequently used social media applications, with most of its users being teenagers or students. The existence of the TikTok phenomenon, which is massive in society, can influence students' learning motivation levels. Therefore, this research aims to determine how much influence the use of the TikTok application has on student learning motivation, especially at the State University of Malang. This research uses quantitative descriptive methods. Data was collected and distributed through a closed questionnaire using Google Form to 32 respondents. Data analysis was carried out using the IBM SPSS Statistics 26 application. This research shows that most respondents use TikTok every day and spend more than 2 hours. The content they access is primarily educational or inspirational. On the other hand, some respondents felt that using TikTok negatively impacted decreasing learning motivation caused by excessive use and lack of control in learning use. The data analysis results show no significant difference between the decrease in student learning motivation and the use of TikTok.